2022
DOI: 10.1021/acsomega.1c06241
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Fabric Architecture and Effect of γ-Radiation on the Mechanical Properties of Jute Fiber Reinforced Polyester Composites

Abstract: The fiber architecture can significantly influence the rate of impregnation of a resin in making composites and the load-bearing ability of individual fibers on testing of the loading directions. Moreover, achieving the maximum mechanical performance of a natural fiber composite selection of yarn liner density and optimization of fabric structure and further modification of the composites remains a great challenge for the composite research community. In this study, a number of jute-based woven derivatives (pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Up to a certain dose (7.50 kGy irradiation), enough chain scission and cross-linking among the molecules of PALF, jute fibre, and LLDPE in composite occurred, as well as mechanical performance was improved. As the gamma radiation was increased, a large amount of chain scission occurred, and the desired characteristics began to deteriorate [ 2 , 11 , 22 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to a certain dose (7.50 kGy irradiation), enough chain scission and cross-linking among the molecules of PALF, jute fibre, and LLDPE in composite occurred, as well as mechanical performance was improved. As the gamma radiation was increased, a large amount of chain scission occurred, and the desired characteristics began to deteriorate [ 2 , 11 , 22 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gamma irradiation is the application of ionising radiation to a specific body with the highest energy and shortest wavelength gamma rays. It can improve the reinforcing fiber's compatibility with the polymer matrix [ 22 ]. As a result, the physico-mechanical properties (tensile strength and modulus, bending or flexural strength and modulus, impact strength, density, dimensional stability, and so on) and thermo-chemical properties (chain scission as well as cross-linking within matrix and reinforcement, interfacial polarisation and orientation, thermal stability, hydrophobicity, glass transition temperature, and so on) of natural fibre reinforced polymer composites increased up to a specific dose [ 2 , 11 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The usual loadings of ordinary filaments, dust, graphite, ferrite, and others were used. All the research showed that the filler support marginally enhanced the mechanical properties of the composites by using regular fiber factor layering, which was incredibly hydrophobic and produced an unfavorable interaction with the hydrophobic grid [19]. Thus, several factors, such as the effect of filler hybridization by combining two charges in a comparable matrix, may influence how mechanically composite materials behave [20].…”
Section: Introductionmentioning
confidence: 99%